Jens Peter Frølund Thomsen, British Politics and Tråde Unions in the 1980s: Governing Against Pressure, Aldershot: Darmouth Publishing Company, 1996, 279 s., GBP 35.50. - Bugge Bertramsen, René (Politica, 1997)
-